Narrative review on the use of sled training to improve sprint performance in team sport athlete - Zabaloy, S.; Freitas, T. T.; Pareja-Blanco, F.; Alcaraz, P. E.; Loturco, I. (Strength and Conditioning Journal, 2023)
Sprinting is a key component for many individual and team sports. Therefore, to enhance sprint performance, various training methods are widely used by coaches and practitioners, including maximum sprint speed and resisted sprint training. Resisted sprinting with sled towing is a method that has recently received considerable attention from the sport science community. However, to date, no consensus exists regarding its acute and chronic effects in team sport athletes. This narrative review aimed to (a) review and analyze the mechanics of sprinting under unresisted and resisted conditions with a specific focus on team sport disciplines; (b) provide a thorough and applied discussion on the importance of considering acute and chronic effects of sled loading on technique, electromyographic activity, and force production, as well as on the role of muscle architecture and neural factors in sled training; (c) analyze the effects of increasing sled loads during acceleration and maximum velocity phases on contact and flight phases, while concomitantly examining kinetic, kinematic, and neuromuscular aspects, because all these factors affect each other and cannot be properly understood in isolation.